Artificial Sweeteners: History and New Concepts on Inflammation - Basson, Abigail Raffner; Rodriguez-Palacios, Alexander; Cominelli, Fabio (Frontiers in Nutrition, 2021)
Since the introduction of artificial sweeteners (AS) to the North American market in the 1950s, a growing number of epidemiological and animal studies have suggested that AS may induce changes in gut bacteria and gut wall immune reactivity, which could negatively affect individuals with or susceptible to chronic inflammatory conditions such as inflammatory bowel disease (IBD), a disorder which is growing exponentially in westernized countries. This review summarizes the history of currently FDA-approved AS, their chemical composition, metabolism and bacterial utilization, and provides a scoping overview of the disease mechanisms associated with the induction or prevention of inflammation in IBD. We provide a general outlook on areas that have been